Unlocking the future of food security through access to finance for sustainable agribusiness performance - Abolade, Ayobami Paul; Lawal, Ibrahim Olanrewaju; Akanbi, Kamoru Lanre; Salami, Ahmed Orilonise (Management and Entrepreneurship: Trends of Development, 2024)
Access to finance is vital for improving food security, particularly in developing nations where agricultural production is crucial. Despite several financial interventions targeted at increasing agricultural production, smallholder farmers continue to lack access to reasonable, timely, and sufficient financing, limiting their ability to invest in improved technology and inputs, lowering productivity and food supply. This study examines the relationship between access to finance and food security among smallholder farmers in Ogun State, employing institutional theory as a theoretical framework. The study takes a quantitative method, with a survey for the research design and a population of 37,200 agricultural smallholder farmers. A sample size of 380 was chosen using probability sampling and simple random techniques. The data were analysed via Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings demonstrate a favourable relationship between access to finance and food security, with an R2-value of 0.615 indicating a robust link. These findings underline the need of improving financial institutions and implementing enabling policies to enable farmers have access to the financial resources they need to achieve food security outcomes. JEL Classification: L26